2015
DOI: 10.1096/fj.14-266783
|View full text |Cite
|
Sign up to set email alerts
|

Glutathione prevents preterm parturition and fetal death by targeting macrophage‐induced reactive oxygen species production in the myometrium

Abstract: Preterm birth is an inflammatory process resulting from the massive infiltration of innate immune cells and the production of proinflammatory cytokines in the myometrium. However, proinflammatory cytokines, which induce labor in vivo, fail to induce labor-associated features in human myometrial cells (MCs). We thus aimed to investigate if reactive oxygen species (ROS) production could be the missing step between immune cell activation and MC response. Indeed, we found that ROS production is increased in the hu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
36
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(36 citation statements)
references
References 73 publications
0
36
0
Order By: Relevance
“…Activated macrophages elevate cytotoxic molecules, such as free radical species and proinflammatory cytokines, which contribute to neurotoxicity in coculture systems3441 and in a murine model42. NAC is a known ROS scavenger that not only ameliorates LPS-induced ROS generation and inflammatory effects in amniotic fluid and placenta, but also increases fetal viability and reduces white matter injury3643.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Activated macrophages elevate cytotoxic molecules, such as free radical species and proinflammatory cytokines, which contribute to neurotoxicity in coculture systems3441 and in a murine model42. NAC is a known ROS scavenger that not only ameliorates LPS-induced ROS generation and inflammatory effects in amniotic fluid and placenta, but also increases fetal viability and reduces white matter injury3643.…”
Section: Resultsmentioning
confidence: 99%
“…Similarly, embryo weight was increased in the 25-μg/kg LPS group, and NAC returned this level close to control (Table 1). Previous studies suggest that LPS-induced oxidative stress and ROS contribute to fetal death3334. NAC may have the capacity to attenuate LPS-induced cerebral white matter injury37.…”
Section: Resultsmentioning
confidence: 99%
“…In addition to these agents, antioxidants are believed to represent a promising treatment option, not only for preterm birth (7,14,24) but also for neonatal disorders, bronchopulmonary dysplasia, retinopathy of prematurity, necrotizing enterocolitis, and periventricular leukomalacia (25). We showed that TRX is one of the potential agents for intrauterine infection/inflammation by its antioxidant and anti-inflammatory properties.…”
Section: Discussionmentioning
confidence: 90%
“…In human gestational tissues (placenta, fetal membranes, and myometrium), treatment with antioxidants (curcumin, naringenin, or apigenin) reduced expression of LPS-induced IL-6, IL-8, and COX-237. In animal models, numerous antioxidants have shown beneficial effects on PTB, fetal death, and intrauterine growth restriction38394041. Thus, oxidative stress strongly correlates with PTB and other adverse birth outcomes, and therapies that reduce oxidative stress could have beneficial effects in reducing the risks of PTB and its associated complications.…”
Section: Discussionmentioning
confidence: 99%